High-elastic SBS-tea powder friction layer, preparation method thereof and application of high-elastic SBS-tea powder friction layer in friction nano-generator

By using hydroxylated SBS and tea powder to prepare a high-elastic SBS-tea powder friction layer and combined with PTFE film, the problem of insufficient elasticity of the existing friction layer is solved, significantly improving the electrical output performance of the friction nanogenerator, and supporting intelligence Long-term energy collection for traffic monitoring systems.

CN119410002AActive Publication Date: 2025-02-11HARBIN INST OF TECH

Patent Information

Application Number
CN202411744858.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-11
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing polymer-based friction layer is insufficiently elastic in friction nanogenerators, limiting its application potential in long-term energy collection and monitoring.

Method used

The high elastic SBS-tea powder friction layer is prepared by using hydroxylated SBS and tea powder as raw materials. Through hydroxylation reaction and magnetic stirring, a film with high elasticity and excellent power generation performance is formed, and a film with polytetrafluoroethylene (PTFE) is used. In combination, negative electrodes for friction nanogenerators.

Benefits of technology

The electrical output characteristics and power generation effects of friction nanogenerators have been improved, and its application potential in vehicle-road coupled intelligent traffic monitoring systems has been enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410002A_ABST
    Figure CN119410002A_ABST
Patent Text Reader

Abstract

The invention discloses a high-elastic SBS-tea powder friction layer, a preparation method thereof and application of the high-elastic SBS-tea powder friction layer in a friction nano-generator. The invention belongs to the technical field of friction nanometer power generation. The invention aims to solve the technical problem that the existing high-molecular polymer-based friction layer is low in elasticity and power generation performance. According to the invention, hydroxylated SBS and tea powder are adopted as raw materials to prepare an SBS-tea powder film for the friction nano-generator, the number of H atoms of a friction layer is increased by using waste tea powder, and more electrons are provided for high electronegativity F atoms of PTFE, so that the electric output characteristic of the friction nano-generator is increased, the power generation effect is greatly improved, and the cost is reduced. And theoretical support is provided for application of the TENG in a vehicle-road coupling intelligent traffic monitoring system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of friction nanogenerator power generation, and specifically relates to a high-elastic SBS-tea powder friction layer and a preparation method thereof and application in a friction nanogenerator. Background Art

[0002] In the transportation industry, achieving sustainable monitoring of transportation systems and using clean energy as a power source has always been one of the core challenges that need to be addressed. In recent years, the research and development of intelligent traffic monitoring and sensing systems has made significant progress. These systems have widely integrated various technologies such as ultrasonic, infrared and acoustic sensors, and are effectively applied to vehicle queue length estimation, driver status monitoring, early detection of vehicle mechanical defects, traffic flow collection, road condition assessment, bridge vibration and displacement monitoring, traffic vehicle tracking and other key areas. However, these sensors generally rely on external power supply, and traditional batteries have limitations such as limited service life, hard and inconvenient shells, and significant environmental impact, which seriously restricts long-term and continuous monitoring operations.

[0003] In view of the above limitations, it is particularly important and urgent to explore and apply clean energy to support long-term monitoring of intelligent transportation systems. As an innovative energy harvesting device, triboelectric nanogenerator (TENG) can collect mechanical energy such as road driving and vehicle vibration and convert it into electrical energy, providing a potential energy solution for intelligent transportation monitoring and sensing systems.

[0004] However, in the development of TENG, how to effectively control the surface charge density to produce devices with excellent triboelectric properties has become one of the most critical and urgent technical challenges to be overcome. Linear polymers containing fluorine atoms with high electron affinity, such as polytetrafluoroethylene (PTFE), have been widely used as negative friction layer materials for TENG, but the lack of elasticity of this material limits the application potential of TENG in long-term energy collection and monitoring. Summary of the invention

[0005] The purpose of the present invention is to solve the technical problem that the existing high molecular polymer-based friction layer has low elasticity and power generation performance, and to provide a high-elastic SBS-tea powder friction layer and a preparation method thereof and an application in a friction nanogenerator.

[0006] One of the purposes of the present invention is to provide a method for preparing a high-elastic SBS-tea powder friction layer, which is carried out according to the following steps:

[0007] Step 1: dissolving linear SBS in chloroform, then adding hydrogen peroxide and formic acid to carry out hydroxylation reaction, adding petroleum ether to the obtained emulsion after the reaction is completed to precipitate the polymer, purifying, vacuum drying, and grinding to obtain hydroxylated SBS;

[0008] Step 2: Dry and grind the brewed waste tea leaves to obtain tea powder, then add the tea powder, silane coupling agent and nano-silicon dioxide (SiO2) to a tetrahydrofuran (THF) solution of hydroxylated SBS, and stir magnetically for a certain period of time at a certain temperature to obtain an SBS-tea powder composite solution, which is then placed in a mold to defoam and solidify into a film under vacuum conditions to obtain a high-elastic SBS-tea powder friction layer.

[0009] It is further defined that the mass ratio of linear SBS to chloroform in step 1 is 1:(5-15).

[0010] It is further defined that in step 1, the mass ratio of hydrogen peroxide to formic acid and chloroform is (0.5-1.5):10:10.

[0011] It is further defined that the hydroxylation reaction temperature in step 1 is 50-70°C and the reaction time is 20-24h.

[0012] It is further defined that the vacuum drying temperature in step 1 is 30-50° C. and the drying time is 20-24 h.

[0013] It is further defined that the content of hydroxylated SBS in the SBS-tea powder composite solution in step 2 is 10-25wt%, the mass ratio of nano-SiO2 and tea powder to hydroxylated SBS is (10-20): (10-20): 100, and the mass ratio of silane coupling agent to nano-SiO2 is (10-20): 100.

[0014] In a further embodiment, the silane coupling agent in step 2 comprises 3-thiopropylmethoxysilane.

[0015] It is further defined that in step 2, magnetic stirring is performed at 400-600 rpm and 50-70° C. for 3-6 hours.

[0016] It is further defined that in step 2, the curing temperature is 60-80° C. and the curing time is 12-24 hours.

[0017] The second object of the present invention is to provide a high-elastic SBS-tea powder friction layer obtained by the above method.

[0018] The third object of the present invention is to provide a friction nanogenerator, wherein the negative electrode of the friction nanogenerator comprises the above-mentioned high-elastic SBS-tea powder friction layer, and the positive electrode comprises a polytetrafluoroethylene (PTFE) film.

[0019] A fourth object of the present invention is to provide a method for preparing a triboelectric nanogenerator, the method comprising the following steps:

[0020] S1: Paste the above-mentioned highly elastic SBS-tea powder friction layer film onto the copper electrode, and then paste the other side of the copper electrode onto an acrylic plate to prepare a negative electrode;

[0021] S2: Paste a polytetrafluoroethylene (PTFE) film onto a copper electrode, and then paste the other side of the copper electrode onto an acrylic plate to prepare a positive electrode;

[0022] S3: Connect the four corners of the two acrylic plates with springs to obtain the SBS-tea powder / PTFE friction nanogenerator.

[0023] A fifth object of the present invention is to provide an application of a friction nanogenerator in a vehicle-road coupled intelligent traffic monitoring system.

[0024] Compared with the prior art, the present invention has the following significant effects:

[0025] The present invention adopts hydroxylated SBS and tea powder as raw materials to prepare SBS-tea powder film for friction nanogenerator. The waste tea powder is used to increase the number of H atoms in the friction layer, providing more electrons for the highly electronegative F atoms of PTFE, thereby increasing the electrical output characteristics of the friction nanogenerator. This not only greatly improves the power generation effect, but also provides theoretical support for the application of TENG in the vehicle-road coupled intelligent traffic monitoring system. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the configuration of the friction nanogenerator;

[0027] Figure 2 for Figure 1 Schematic diagram of the structure of the positive friction layer and the negative friction layer;

[0028] Figure 3 This is a connection diagram of the friction nanogenerator test system;

[0029] Figure 4 for Figure 3 Schematic diagram of the structure of the middle movement module;

[0030] In the accompanying drawings, the components represented by the reference numerals are as follows:

[0031] 1-Acrylic plate A, 2-Conductive copper electrode A, 3-Negative friction layer, 4-Acrylic plate B, 5-Conductive copper electrode B, 6-Positive friction layer, 7-Support spring, 8-Bottom plate, 9-Integrated drive-controlled stepper motor, 10-Motion module, 11-Movers, 12-Stators, 13-Power supply, 14-Computer, 15-Acquisition module, 16-Electrometer, 17-Motion module. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0034] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0035] The "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0036] The endpoints and any values ​​of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0037] Example 1: The preparation method of the high elastic SBS-tea powder friction layer of this example is carried out according to the following steps:

[0038] Step 1: Add 25g of linear SBS (Liaoning North Dynasol Synthetic Rubber Co., Ltd., Dynasol 501h, PB ratio of 7:3) powder and 250g of chloroform to a three-necked flask equipped with a condenser, mechanical stirring and a thermometer, start stirring, and heat to 50°C to completely dissolve the SBS. Then add 25g of hydrogen peroxide and 250g of formic acid solution to the flask, and react continuously at 60°C for 24h. After the reaction is completed, cool and discharge the material. Pour the obtained polymer emulsion into a beaker, and add 250g of petroleum ether to precipitate the polymer from the mixed solvent. Repeat the precipitation operation 3 times, purify the product, put the obtained polymer sample into a vacuum drying oven, vacuum dry it at 40°C for 24h, grind it to more than 200 mesh, and obtain hydroxylated SBS powder;

[0039] Step 2: Collect the brewed waste green tea leaves (Huangshan Maofeng), add water and continue soaking for 24 hours, and then place them in an oven for drying at 70°C for 24 hours. After drying, grind them into 500 meshes to obtain green tea powder.

[0040] Weigh 25 g of hydroxylated SBS powder, dissolve it in 67 g of THF solution, stir evenly, and place it in a magnetic stirrer at 60° C. and 500 rpm for 6 h to obtain a THF solution of hydroxylated SBS.

[0041] 0.5 g of 3-thiopropylmethoxysilane, 2.5 g of nano-SiO2 and 5 g of green tea powder were added to the SBS / THF solution, and the solution was placed in a magnetic stirrer and stirred at 500 rpm for 5 h at 60 ° C to obtain a SBS-green tea powder composite solution. Finally, the SBS-green tea powder composite solution was placed in a 3D printed mold, placed in a vacuum oven to remove bubbles, and cured at 70 ° C for 24 h to obtain a 100 μm thick SBS-tea powder film. (As shown in Figure 2) Figure 2 shown).

[0042] Application example 1: Combination Figure 1 The preparation method of the friction nanogenerator comprises the following steps:

[0043] First, the SBS-tea powder film and PTFE film of Example 1 were cut into 2 cm*2 cm;

[0044] Secondly, the SBS-tea powder film was pasted onto a conductive copper electrode, and the other side of the copper electrode was pasted onto an acrylic plate to prepare a negative electrode.

[0045] Then, the PTFE film was pasted onto the conductive copper electrode, and the other side of the copper electrode was pasted onto the acrylic plate to prepare a positive electrode;

[0046] Finally, the two acrylic plates were connected at the four corners with springs to obtain the SBS-tea powder / PTFE friction nanogenerator.

[0047] Combination Figure 3-4 , a friction nanogenerator test system was built to test the friction nanogenerator. During the test, the positive electrode was pasted on the vertical plate of the stator 12 in the motion module 17, and the negative electrode was pasted on the vertical plate of the mover 11 in the motion module 17. The Keithley 6517B electrometer 16, the motion module 17, and the acquisition module 15 were controlled, and the high-speed signal acquisition card was used to perform high-frequency sampling of the current and voltage signals obtained in the test. The maximum open circuit voltage of Example 1 was measured. At 10Hz, the maximum open circuit voltage of Example 1 was 189V.

[0048] Example 2: The preparation method of the high elastic SBS-tea powder friction layer of this example is carried out according to the following steps:

[0049] Step 1: Add 25g of linear SBS (Liaoning North Dynasol Synthetic Rubber Co., Ltd., Dynasol 501h, PB ratio of 7:3) and 250g of chloroform to a three-necked flask equipped with a condenser, mechanical stirring and a thermometer, start stirring, and heat to 50°C to completely dissolve the SBS. Then add 25g of hydrogen peroxide and 250g of formic acid solution to the flask, and react continuously at 60°C for 24h. After the reaction is completed, cool and discharge the material. Pour the obtained polymer emulsion into a beaker, and add 250g of petroleum ether to precipitate the polymer from the mixed solvent. Repeat the precipitation operation 3 times, purify the product, put the obtained polymer sample into a vacuum drying oven, vacuum dry it at 40°C for 24h, grind it to more than 200 mesh, and obtain hydroxylated SBS powder;

[0050] Step 2: Collect the brewed waste green tea leaves (Huangshan Maofeng), add water and continue soaking for 24 hours, and then place them in an oven for drying at 70°C for 24 hours. After drying, grind them into 500 meshes to obtain green tea powder.

[0051] Weigh 25 g of hydroxylated SBS powder, dissolve it in 68.25 g of THF solution, stir evenly, and place it in a magnetic stirrer at 60° C. and 500 rpm for 6 h to obtain a THF solution of hydroxylated SBS.

[0052] 0.5 g of 3-thiopropylmethoxysilane, 2.5 g of nano-SiO2 and 3.75 g of green tea powder were added to the SBS / THF solution, and the solution was stirred at 500 rpm for 5 h at 60 ° C to obtain a SBS-green tea powder composite solution. Finally, the SBS-green tea powder composite solution was placed in a 3D printed mold, placed in a vacuum oven to remove bubbles, and cured at 70 ° C for 24 h to obtain a 100 μm thick SBS-tea powder film. (As shown in Figure 2) Figure 2 shown).

[0053] Application Example 2: Combination Figure 1 The preparation method of the friction nanogenerator comprises the following steps:

[0054] First, the SBS-tea powder film and PTFE film of Example 2 were cut into 2 cm*2 cm;

[0055] Secondly, the SBS-tea powder film was pasted onto a conductive copper electrode, and the other side of the copper electrode was pasted onto an acrylic plate to prepare a negative electrode.

[0056] Then, the PTFE film was pasted onto the conductive copper electrode, and the other side of the copper electrode was pasted onto the acrylic plate to prepare a positive electrode;

[0057] Finally, the two acrylic plates were connected at the four corners with springs to obtain the SBS-tea powder / PTFE friction nanogenerator.

[0058] The electrical output performance test method is the same as that in Application Example 1. The maximum open circuit voltage of Example 2 is measured. At 10 Hz, the maximum open circuit voltage of Example 2 is 170V.

[0059] Example 3: The preparation method of the high elastic SBS-tea powder friction layer of this example is carried out according to the following steps:

[0060] Step 1: Add 25g of linear SBS (Liaoning North Dynasol Synthetic Rubber Co., Ltd., Dynasol 501h, PB ratio of 7:3) and 250g of chloroform to a three-necked flask equipped with a condenser, mechanical stirring and a thermometer, start stirring, and heat to 50°C to completely dissolve the SBS. Then add 25g of hydrogen peroxide and 250g of formic acid solution to the flask, and react continuously at 60°C for 24h. After the reaction is completed, cool and discharge the material. Pour the obtained polymer emulsion into a beaker, and add 250g of petroleum ether to precipitate the polymer from the mixed solvent. Repeat the precipitation operation 3 times, purify the product, put the obtained polymer sample into a vacuum drying oven, vacuum dry it at 40°C for 24h, grind it to more than 200 mesh, and obtain hydroxylated SBS powder;

[0061] Step 2: Collect the brewed waste green tea leaves (Huangshan Maofeng), add water and continue soaking for 24 hours, and then place them in an oven for drying at 70°C for 24 hours. After drying, grind them into 500 meshes to obtain green tea powder.

[0062] Weigh 25 g of hydroxylated SBS powder, dissolve it in 69.5 g of THF solution, stir evenly, and place it in a magnetic stirrer at 60° C. and 500 rpm for 6 h to obtain a THF solution of hydroxylated SBS.

[0063] 0.5 g of 3-thiopropylmethoxysilane, 2.5 g of nano-SiO2 and 2.5 g of green tea powder were added to the SBS / THF solution, and the solution was stirred at 500 rpm at 60 ° C for 5 h to obtain a SBS-green tea powder composite solution. Finally, the SBS-green tea powder composite solution was placed in a 3D printed mold, placed in a vacuum oven to remove bubbles, and cured at 70 ° C for 24 h to obtain a 100 μm thick SBS-tea powder film. (As shown in Figure 2) Figure 2 shown).

[0064] Application Example 3: Combination Figure 1 The preparation method of the friction nanogenerator comprises the following steps:

[0065] First, the SBS-tea powder film and PTFE film of Example 3 were cut into 2 cm*2 cm;

[0066] Secondly, the SBS-tea powder film was pasted onto a conductive copper electrode, and the other side of the copper electrode was pasted onto an acrylic plate to prepare a negative electrode.

[0067] Then, the PTFE film was pasted onto the conductive copper electrode, and the other side of the copper electrode was pasted onto the acrylic plate to prepare a positive electrode;

[0068] Finally, the two acrylic plates were connected at the four corners with springs to obtain the SBS-tea powder / PTFE friction nanogenerator.

[0069] The electrical output performance test method is the same as that in Application Example 1. The maximum open circuit voltage of Example 3 is measured. At 10 Hz, the maximum open circuit voltage of Example 3 is 155V.

[0070] Comparative Example 1: The preparation method of the SBS film of this embodiment is carried out according to the following steps:

[0071] Step 1: Add 25g of linear SBS (Liaoning North Dynasol Synthetic Rubber Co., Ltd., Dynasol 501h, PB ratio of 7:3) and 250g of chloroform to a three-necked flask equipped with a condenser, mechanical stirring and a thermometer, start stirring, and heat to 50°C to completely dissolve the SBS. Then add 25g of hydrogen peroxide and 250g of formic acid solution to the flask, and react continuously at 60°C for 24h. After the reaction is completed, cool and discharge the material. Pour the obtained polymer emulsion into a beaker, and add 250g of petroleum ether to precipitate the polymer from the mixed solvent. Repeat the precipitation operation 3 times, purify the product, put the obtained polymer sample into a vacuum drying oven, vacuum dry it at 40°C for 24h, grind it to more than 200 mesh, and obtain hydroxylated SBS powder;

[0072] Step 2: Weigh 25g of hydroxylated SBS powder, dissolve it in 72g of THF solution, stir evenly, and place it in a magnetic stirrer for magnetic stirring at 60°C and 500rpm for 6h to obtain a THF solution of hydroxylated SBS. Add 0.5g of 3-thiopropylmethoxysilane and 2.5g of nano-SiO2 to the SBS / THF solution, continue to place it in a magnetic stirrer for magnetic stirring at 60°C and 500rpm for 5h to obtain an SBS solution. Finally, place the SBS solution in a 3D printed mold, place it in a vacuum oven to remove bubbles, and cure it at 70°C for 24h to obtain a 100μm thick SBS film. (As shown in Figure 2 shown).

[0073] Comparative application example 1: Combination Figure 1 The preparation method of the friction nanogenerator comprises the following steps:

[0074] First, the SBS film and PTFE film of Comparative Example 1 were cut into 2 cm*2 cm pieces;

[0075] Secondly, the SBS film was pasted onto the conductive copper electrode, and the other side of the copper electrode was pasted onto an acrylic plate to prepare a negative electrode.

[0076] Then, the PTFE film was pasted onto the conductive copper electrode, and the other side of the copper electrode was pasted onto the acrylic plate to prepare a positive electrode;

[0077] Finally, the two acrylic plates were connected at the four corners with springs to obtain the SBS / PTFE friction nanogenerator.

[0078] The electrical output performance test method is the same as that in Application Example 1. The maximum open circuit voltage of Comparative Example 1 is measured. At 10 Hz, the maximum open circuit voltage of Comparative Example 1 is 120V.

[0079] The SBS-tea powder / PTFE friction nanogenerator developed by the present invention has a higher open circuit voltage because the chemical components in the waste tea powder can enhance the charge transfer between the SBS-tea powder film and the PTFE friction layer. The waste tea powder is used to increase the number of H atoms in the friction layer, providing more electrons for the highly electronegative F atoms of PTFE, thereby increasing the electrical output characteristics of the friction nanogenerator.

[0080] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a high-elastic SBS-tea powder friction layer, characterized in that: The method: Step 1: dissolving linear SBS in chloroform, then adding hydrogen peroxide and formic acid to carry out hydroxylation reaction, adding petroleum ether to the obtained emulsion after the reaction is completed to precipitate the polymer, purifying, vacuum drying, and grinding to obtain hydroxylated SBS; Step 2: Dry and grind the brewed waste tea leaves to obtain tea powder, then add the tea powder, silane coupling agent and nano-SiO2 into the THF solution of hydroxylated SBS, and stir magnetically for a certain time at a certain temperature to obtain an SBS-tea powder composite solution, which is then placed in a mold to defoam and solidify into a film under vacuum conditions to obtain a high-elastic SBS-tea powder friction layer.

2. The method according to claim 1, characterized in that In step 1, the mass ratio of linear SBS to chloroform is 1:(5-15), and the mass ratio of hydrogen peroxide to formic acid and chloroform is (0.5-1.5):10:

10.

3. The method according to claim 1, characterized in that In step 1, the hydroxylation reaction temperature is 50-70° C. and the reaction time is 20-24 h.

4. The method according to claim 1, characterized in that: In step 2, the content of hydroxylated SBS in the SBS-tea powder composite solution is 10-25wt%, the mass ratio of nano-SiO2 and tea powder to hydroxylated SBS is (10-20): (10-20): 100, and the mass ratio of silane coupling agent to nano-SiO2 is (10-20):

100.

5. The method according to claim 1, characterized in that: The silane coupling agent includes 3-thiopropylmethoxysilane.

6. The method according to claim 1, characterized in that In step 2, magnetic stirring is performed at 50-70° C. at a speed of 400-600 rpm for 3-6 hours, the curing temperature is 60-80° C., and the curing time is 12-24 hours.

7. The high-elastic SBS-tea powder friction layer obtained by the method described in any one of claims 1 to 6.

8. A friction nanogenerator, characterized in that: The negative electrode of the friction nanogenerator comprises the high-elastic SBS-tea powder friction layer described in claim 7, and the positive electrode comprises a PTFE film.

9. The method for preparing the triboelectric nanogenerator according to claim 8, characterized in that: The method steps are as follows: S1 pastes the highly elastic SBS-tea powder friction layer film onto the copper electrode, and then pastes the other side of the copper electrode onto an acrylic plate to prepare a negative electrode; S2: Paste the PTFE film onto the copper electrode, and then paste the other side of the copper electrode onto an acrylic plate to prepare a positive electrode; S3: Connect the four corners of the two acrylic plates with springs to obtain the SBS-tea powder / PTFE friction nanogenerator.

10. Application of the triboelectric nanogenerator according to claim 8 in a vehicle-road coupled intelligent traffic monitoring system.

Citation Information

Patent Citations

  • Friction layer of nano-generator, preparation method of friction layer and application of friction layer in friction nano-generator

    CN115694245A

  • Modified triboelectrification material for triboelectric nano-generator, preparation method of modified triboelectrification material and triboelectric nano-generator

    CN116239812A

  • Sofa having Movable Back

    KR1020210007693A

  • Additive for high early strength cement comprising modified sulfur binder, method for preparing the same, high early strength cement conctrete composition comprising the same, and high early strength cement conctrete composition

    KR102335008B1

Cited By

  • PDMS / PTFE (Polydimethylsiloxane / Polytetrafluoroethylene) friction nano-generator based on biological topological structure and preparation method of PDMS / PTFE friction nano-generator

    CN120209580A